2012
DOI: 10.5194/bgd-9-14945-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial and temporal variability of N<sub>2</sub>O emissions in a subtropical forest catchment in China

Abstract: Subtropical forests in South China have received chronically large amounts of atmogenic nitrogen (N) causing N saturation. Recent studies suggest that a significant proportion of the N input is returned to the atmosphere, in part as nitrous oxide (N2O). We measured N2O emission fluxes by closed chamber technique throughout two years in a Masson pine-dominated headwater catchment with acrisols (pH ~ 4) at TieShanPing (Chongqing, SW China) and assessed the spatial and temporal variability i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 58 publications
3
28
0
Order By: Relevance
“…The rates of N 2 O emission observed from the controls of AA and EU plantations (1.9 to 2.3 kg N 2 O-N ha −1 yr −1 ) are comparable with previous reports in (sub)tropical regions of southern China (2.0 to 4.8 kg N 2 O-N ha −1 yr −1 ) (Zhang et al, 2008;Zhu et al, 2013a), and also within the range of published results (1.2-2.6 kg N 2 O-N ha −1 yr −1 ) from other tropical forests (Werner et al, 2007;Gharahi Ghehi et al, 2012). Higher rates of N 2 O emissions (3.7-7.5 kg N 2 O-N ha −1 yr −1 ) than our study were also reported from tropical forests (Keller and Reiners, 1994;Kiese and ButterbachBahl, 2002).…”
Section: Comparisons Of N 2 O Emissionsupporting
confidence: 88%
See 1 more Smart Citation
“…The rates of N 2 O emission observed from the controls of AA and EU plantations (1.9 to 2.3 kg N 2 O-N ha −1 yr −1 ) are comparable with previous reports in (sub)tropical regions of southern China (2.0 to 4.8 kg N 2 O-N ha −1 yr −1 ) (Zhang et al, 2008;Zhu et al, 2013a), and also within the range of published results (1.2-2.6 kg N 2 O-N ha −1 yr −1 ) from other tropical forests (Werner et al, 2007;Gharahi Ghehi et al, 2012). Higher rates of N 2 O emissions (3.7-7.5 kg N 2 O-N ha −1 yr −1 ) than our study were also reported from tropical forests (Keller and Reiners, 1994;Kiese and ButterbachBahl, 2002).…”
Section: Comparisons Of N 2 O Emissionsupporting
confidence: 88%
“…In the study, N 2 O fluxes showed positive linear relationships with soil temperatures and WFPS, which were consistent with tropical and subtropical forests (Butterbach-Bahl et al, 2004;Zhang et al, 2008;Zhu et al, 2013a). There is a covariation between soil temperature and WFPS in the monsoon climate zone of southern China.…”
Section: Effects Of Soil Temperature and Wfps On N 2 O Emissionsupporting
confidence: 77%
“…This secondary tropical forest in wet seasons thus has favorable conditions for denitrification to emit considerable amounts of N 2 O, i.e., low oxygen content due to high water-filled pore-space (WFPS) and temperature high enough to allow microbial activity to occur. In some tropical and subtropical forests, denitrification contributed more than 70% of soil N 2 O emission43. In the present study, the SEM shows that soil NO 3 − was significantly associated with soil N 2 O emission, and the model totally explained 58% of the variation of soil N 2 O emission in wet seasons.…”
Section: Discussionsupporting
confidence: 51%
“…The TSP catchment is mainly composed of hillslopes, characterized by well‐drained soils (Haplic Acrisol; WRB, ; Zhu et al, ). Water interflow over the argic horizon (which has a high clay content typical for Acrisols) on the hillslope is laterally discharged into the terraced valley bottom of the catchment, where soils are mainly Cambisols (WRB, ) with low hydraulic conductivity.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we quantify CH 4 fluxes weekly to biweekly in a subtropical, N‐saturated forested catchment (Tieshanping, TSP) in SW China over a 3‐year period, including wet and dry summers. The catchment mainly consists of hillslopes with well‐drained soils, where interflow over the argic horizon is laterally transferred to a small area in the valley bottom (groundwater discharge zone), resulting in water saturation following intensive rain episodes (Zhu et al, ). Sampling was conducted along a topographic gradient at four landscape elements, including hillslope, foot of the hillslope, valley bottom, and groundwater discharge zone.…”
Section: Introductionmentioning
confidence: 99%